Study of recombination mechanisms in crystals GaSe doped with Cu, Cd AND Sn - Evtodiev, Igor (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2005)
The energetic diagram of the localized states in the forbidden band energy of the crystals ε-GaSe doped with Cu, Cd and Sn is determined from the analysis of absorption spectra in the field of impurity band, luminescent emissive spectra and thermo luminescent ones.